2020
DOI: 10.35459/tbp.2019.000108
|View full text |Cite
|
Sign up to set email alerts
|

Research on Students' Understanding of Michaelis-Menten Kinetics and Enzyme Inhibition: Implications for Instruction and Learning

Abstract: ABSTRACT We report a summary of the results from an education research project that investigated student reasoning related to Michaelis-Menten enzyme kinetics and enzyme inhibition. We have previously discussed students' mathematical reasoning related to rate laws and reaction order, student conceptions of different types of enzyme inhibition (competitive, noncompetitive, and uncompetitive), and student understanding of representations used to describe enzyme kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 89 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…This lack of scholarship is likely due in part to small populations (N typically less than 20) in these courses that limit possible experimental designs, data collection techniques, and statistical power for analyses associated with studies of affect. These limited-sized populations, though, have been more suited to cognitive-focused work in upper-division courses that has in turn resulted in associated literature reviews (e.g., Bain et al, 2014;Bain and Towns, 2016;Rodriguez and Towns, 2020). While insights into the affective experiences of students in general chemistry and organic chemistry courses exist (e.g., Villafan ˜e et al, 2016;Liu et al, 2017Liu et al, , 2018Gibbons et al, 2018;Raker et al, 2019), there is limited understanding of how findings from experiences of students in gateway chemistry courses translate into more homogeneously populated courses (e.g., majors-focused courses which are often upperdivision courses).…”
Section: Introductionmentioning
confidence: 99%
“…This lack of scholarship is likely due in part to small populations (N typically less than 20) in these courses that limit possible experimental designs, data collection techniques, and statistical power for analyses associated with studies of affect. These limited-sized populations, though, have been more suited to cognitive-focused work in upper-division courses that has in turn resulted in associated literature reviews (e.g., Bain et al, 2014;Bain and Towns, 2016;Rodriguez and Towns, 2020). While insights into the affective experiences of students in general chemistry and organic chemistry courses exist (e.g., Villafan ˜e et al, 2016;Liu et al, 2017Liu et al, , 2018Gibbons et al, 2018;Raker et al, 2019), there is limited understanding of how findings from experiences of students in gateway chemistry courses translate into more homogeneously populated courses (e.g., majors-focused courses which are often upperdivision courses).…”
Section: Introductionmentioning
confidence: 99%
“…A concept inventory, consisting of 24 multiple choice and two multiple select questions, was administered three times: before any instruction, immediately after the cereal-crushing activity, and after all instruction on enzymes, energy, and metabolism (three to four weeks after the cereal activity). The questions were influenced by recent studies of student reasoning and misconceptions (Rodriguez et al, 2019; Rodriguez & Towns, 2020; Shi et al, 2017; Halim et al, 2018; Bain & Towns, 2018) and included questions using cereal as analogy for thermodynamic concepts. Some assessment items were from the Enzyme-Substrate Interactions Concept Inventory (ESICI) (Bretz & Linenberger, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Interviews, concept inventories, and writing exercises conducted by several research groups have identified common challenges and misconceptions relating to energy, enzyme kinetics, and enzymatic interactions (Bretz & Linenberger, 2012; Halim et al, 2018) that we have taken into consideration in our instructional plan. Challenges include visualizing V max and K m (Runge et al, 2006; Darling et al, 2021; Berndsen et al, 2020), interpreting graphs with rates or unfamiliar representations of time (Rodriguez et al, 2019; Rodriguez & Towns, 2020), and identifying if energy is absorbed or released when bonds form or are broken (Bain & Towns, 2018). Fostering student reasoning of core concepts that relate to diverse disciplinary contexts may help to reinforce learning of Gibbs energy and enzyme kinetics that are often presented as separate topics in texts (Bain & Towns, 2018; Bearne, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has shown that students have difficulty discussing the concept of reaction rate, often conflating chemical kinetics with equilibrium , , rate with time, ,, or rate with rate constant . Furthermore, for advanced chemistry topics that build on chemical kinetics, such as enzyme kinetics, other challenges have been reported related to vocabulary, as well as the use of representations such as graphs and equations. ,, In this study, we focus on students’ reasoning related to reaction rate, in which students constructed a graphical model to describe how reaction rate changes over time. Here, we view student-drawn graphs as models, in which the specific shapes of the graphs can be used to explain what is happening within the target system.…”
mentioning
confidence: 99%